THE INFLUENCE OF TEACHERS' TEACHING STYLE, CREATIVITY, AND TEACHING SKILLS ON STUDENT LEARNING MOTIVATION AT SMK NEGERI 25 JAKARTA - Anggrainy, Melya; Zulaihati, Sri; Wahono, Puji (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This study aims to analyze the influence of teaching style, creativity, and teaching skills on student learning motivation at SMK Negeri 25 Jakarta. This study uses a quantitative approach with a population of 358 students, then the research sample is determined as many as 188 students. Data collection was carried out through the distribution of questionnaires that used a 5-point Likert scale to measure the variables studied. Data processing and analysis were carried out using the SPSS version 25 program. The analysis process includes validity test, reliability test, normality test, linearity test, multiple linear regression analysis, F test, T test, and calculation of the determination coefficient. The research findings indicate that teaching style, creativity, and teaching skills, both partially and simultaneously, significantly influence student motivation at SMK Negeri 25 Jakarta.